2015
DOI: 10.1016/j.sajb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress effect on the phytochemistry and antioxidant activity of a South African bulbous geophyte, Gethyllis multifolia L. Bolus

Abstract: a b s t r a c tGethyllis multifolia is a South African bulbous geophyte with medicinal properties and on which very limited research has been conducted. This research investigated the effect of drought and shade, which are experienced in the natural habitat, on the antioxidant properties, as well as the isolation of natural compounds from certain plant parts. The total polyphenol, flavonol/flavone and flavanone contents, oxygen radical absorbance capacity (ORAC), ferric reducing antioxidant power (FRAP) and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…After 5 min, 100 μL (7.5%) aqueous sodium carbonate (Na 2 CO 3 ) (Sigma-Aldrich, South Africa) was added to each well. The method described by Daniels et al [ 56 ] was used to obtain the absorbance reading of the solution in the microplates, and results were expressed as mg gallic acid equivalents per g dry weight (mg GAE/g DW). The flavonol content was determined using quercetin, and the protocol was based on the method described by Daniels et al [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 5 min, 100 μL (7.5%) aqueous sodium carbonate (Na 2 CO 3 ) (Sigma-Aldrich, South Africa) was added to each well. The method described by Daniels et al [ 56 ] was used to obtain the absorbance reading of the solution in the microplates, and results were expressed as mg gallic acid equivalents per g dry weight (mg GAE/g DW). The flavonol content was determined using quercetin, and the protocol was based on the method described by Daniels et al [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Daniels et al [33] found an increase in non-enzymatic antioxidant capacity based on total polyphenol content in bulbs and roots of South African bulbous geophyte Gethyllis multifolia L. Bolus under drought stress. Additionally, Peksel et al [34] showed that Asphodelus aestivus has powerful antioxidant activity that is based on non-enzymatic antioxidants.…”
Section: Discussionmentioning
confidence: 87%
“…According to Kannan and Priya (2020) all ecotypes had the phytochemicals screened regardless of the part containing the compound, with exception of glycosides which were absent in white and black variants (Table 1). Phytochemicals composition is very much affected by environmental stresses, absence or presence of these compounds can be used as a measure the effects of stresses (Daniels et al, 2015).…”
Section: Green Black Stemmentioning
confidence: 99%